2006
DOI: 10.1186/1471-2156-7-15
|View full text |Cite
|
Sign up to set email alerts
|

QTL for microstructural and biophysical muscle properties and body composition in pigs

Abstract: Background: The proportion of muscle fibre types and their size affect muscularity as well as functional properties of the musculature and meat quality. We aimed to identify QTL for microstructural muscle properties including muscle fibre size, their numbers and fibre type proportions as well as biophysical parameters of meat quality and traits related to body composition, i.e. pH, conductivity, area of M. longissimus dorsi and lean meat content. A QTL scan was conducted in a porcine experimental population th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(19 citation statements)
references
References 64 publications
2
17
0
Order By: Relevance
“…We assigned these genes to porcine regions 5q24‐q25, 9p21, 5p15, 9p12 and 6q11–22 respectively, which are in agreement with comparative mapping results 11 . There are several putative QTL for pig backfat thickness, 12 loin eye area 13 and diameter of muscle fibre 14 in the chromosomal regions where these genes mapped. In addition, BTG1 and TOB2 have significant effects on muscle development 15–18 …”
supporting
confidence: 78%
“…We assigned these genes to porcine regions 5q24‐q25, 9p21, 5p15, 9p12 and 6q11–22 respectively, which are in agreement with comparative mapping results 11 . There are several putative QTL for pig backfat thickness, 12 loin eye area 13 and diameter of muscle fibre 14 in the chromosomal regions where these genes mapped. In addition, BTG1 and TOB2 have significant effects on muscle development 15–18 …”
supporting
confidence: 78%
“…Multiple regions were found that had a high frequency of ROH across both the maternal breeds whereas one region was detected across all three breeds. The regions on SSC1 (248.7–264.2 Mb), SSC4 (42.1–61.3 Mb) and SSC14 (98.0–111.7 Mb) detected in LW and LA were previously shown to impact meat and carcass quality [4851], multiple production and meat quality traits [52, 53], and reproduction [54], respectively. Four regions were found to have a higher frequency of ROH5 and/or ROH10 across the terminal DU breed and both the maternal breeds.…”
Section: Discussionmentioning
confidence: 99%
“…Collecting muscle fiber type phenotypic data is a very laborious and complicated process; thus only 120 out of 1,912 F 2 individuals were phenotyped. Until now, little research has been done regarding the identification of QTLs or SNPs associated with these traits [7][8][9]11,12]. In our previous study, the following QTLs were identified within the same sample population: 3 QTLs associated with IIB_A on SSC7, SSC8, and SSC15; 3 QTLs associated with IIA_A on SS7 and SSC11; 1 QTL associated with FN on SSC7; and 1 QTL associated with I_NP on SSCX.…”
Section: Discussionmentioning
confidence: 98%
“…Fifteen significant QTLs were associated with muscle fiber traits in a Japanese wild boar ×Large White population [7]. Thirteen QTLs for muscle fiber composition were identified in a Duroc×Berlin Miniature cross population [8]. Estellé et al [9] detected 20 significant genome regions associated with muscle fiber traits in an Iberian× Landrace F 2 pig population.…”
Section: Introductionmentioning
confidence: 99%